2016
DOI: 10.22456/1679-9216.80931
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and Gel Platelet Rich Plasma as Skin Healing Adjuvant

Abstract: Background: In recent decades, many researches have been conducted on processes involved in tissue repairing, mainly in the development of resources and technology designed to improve the wound healing progress. Platelet rich plasma (PRP) derived from autologous blood is defined as a plasma volume with platelet concentration higher than physiological level. It is an autogenous and low cost source of growth factors, which are essential for tissue regeneration due to their angiogenic, mitogenic, and chemotactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(7 reference statements)
0
3
0
1
Order By: Relevance
“…Regarding the centrifugation method, it can be single or double centrifugation. The present study opted for the double centrifugation protocol, recommended by Landsberg et al 20 and by Garcez et al, 21 having been shown to be effective, since an increase of at least 100% in the number of platelets was observed. There were also increases in the amount of platelets close to 200%, making it possible to obtain even more favorable results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Regarding the centrifugation method, it can be single or double centrifugation. The present study opted for the double centrifugation protocol, recommended by Landsberg et al 20 and by Garcez et al, 21 having been shown to be effective, since an increase of at least 100% in the number of platelets was observed. There were also increases in the amount of platelets close to 200%, making it possible to obtain even more favorable results.…”
Section: Discussionmentioning
confidence: 92%
“…Em relação ao método de centrifugação, pode ser centrifugação única ou dupla. O presente estudo optou pelo protocolo de centrifugação dupla, recomendado por Landesberg et al 20 e Garcez et al, 21 tendo se mostrado eficaz, com aumento de ao menos 100% no número de plaquetas. Também houve aumento na quantidade de plaquetas próximo a 200%, possibilitando a obtenção de resultados ainda mais favoráveis.…”
Section: Discussionunclassified
“…Finally, the sample showed a platelet pellet and plasma. The platelet pellet was collected with 1 mL of plasma, with the counting of various cells, and transferred into an insulin syringe (Garcez et al, 2016; Table 1). Following muscle closure, approximately 0.25 mL of PRP was injected on each side along the suture line of the muscle layer, and another 0.25 mL of PRP was injected on each side along the suture line of the dermis layer.…”
Section: Operative Detailsmentioning
confidence: 99%
“…O PRP tem sido descrito como alternativa simples e barata para o tratamento de diversas lesões, promovendo liberação de fatores pró-cicatriciais (Boswell et al, 2012;Wasterlain et al, 2016) e estimulando a expressão e transcrição gênica de substâncias que auxiliam no processo de reparação tecidual (Romero et al, 2017) e assim, seu uso em diferentes espécies tem obtido sucesso na cicatrização de lesões de pele (Garcez et al, 2016), cartilagem (Coskun et al, 2019;Yamada et al, 2016) e tendões (Bazzano et al, 2013;Maia et al, 2009). Diante disso, o objetivo desta revisão foi levantar dados na literatura sobre a obtenção, utilização e efeitos do PRP no tratamento de lesões tendíneas na espécie equina.…”
Section: Introductionunclassified